2018
DOI: 10.1088/1361-6455/aa9eaf
|View full text |Cite
|
Sign up to set email alerts
|

Ion guiding in macro-size insulating capillaries: straight, tapered, and curved shapes

Abstract: When keV energy ions are injected into a tilted insulating capillary, a certain fraction of the injected ions are transported through the tilt angle of the capillary. This ion guiding phenomenon is considered to be caused by a self-organizing charge distribution, where the inner wall of the capillary becomes charged by initial incoming ions. The charge distribution, which is formed, can guide following ions toward the exit of the capillary. Since the initial discovery of this effect, studies of ion guiding by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…Bombarding beams including highly and singly charged ions [1,2,18], electrons [3][4][5]19], and even exotic particles [20,21] have been proposed or tested. These studies have been summarized in three review articles [22][23][24]. Simulations and theoretical models of the charge buildup and particle transport through capillaries are also outlined in these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Bombarding beams including highly and singly charged ions [1,2,18], electrons [3][4][5]19], and even exotic particles [20,21] have been proposed or tested. These studies have been summarized in three review articles [22][23][24]. Simulations and theoretical models of the charge buildup and particle transport through capillaries are also outlined in these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…a fraction of the injected beam will continue the charge-deposition to replace the charge loss due to the leakage currents, while the rest of the beam is guided through the capillary. A summary of these studies and their findings can be found in several review articles 2 4 . In general, however, the experimental studies have been qualitative in nature, e.g., typically an unknown portion of the beam is injected into the capillary and the guided beam intensity has been studied as a function of time after beam injection.…”
Section: Introductionmentioning
confidence: 99%
“…a fraction of the injected beam will continue the charge-deposition to replace the charge loss due to the leakage currents, while the rest of the beam is guided through the capillary. A summary of these studies and their findings can be found in several review articles [2][3][4]. In general, however, the experimental studies have been qualitative in nature, e.g., typically the guided beam intensity has been studied as a function of time after beam injection.…”
Section: Introductionmentioning
confidence: 99%